POTRET PENDIDIKAN KELUARGA DALAM AL-QURâAN ( Telaah QS. AT-Tahrim Ayat 6 ) - fakhrurrazi, Fakhrurrazi (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Dawah of IAIN Langsa, 2018)
The Quran is one source of law and legal propositions. The Quran is a source of knowledge. Family coaching as the main pillar of Islamic education which is connected with Allahs command in the Quran, as in Q.S. At-Tahri>m [66]: 6, Allah commands those who believe to protect themselves and their families from the fire of hell, whose fuel consists of humans and stones, obediently and obediently carrying out the commands of Allah swt